2002
DOI: 10.1046/j.1365-2648.2002.02147.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of massage on pain and anxiety during labour: a randomized controlled trial in Taiwan

Abstract: Findings suggest that massage is a cost-effective nursing intervention that can decrease pain and anxiety during labour, and partners' participation in massage can positively influence the quality of women's birth experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
2
28

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(135 citation statements)
references
References 21 publications
4
101
2
28
Order By: Relevance
“…Therefore, the result of this study could support the use of soothing music together with other nursing interventions in reducing the pain experienced by women during the latent phase of labor. However, it is essential to note that music intervention was administered only during the latent phase of labor, pain increases as labor progresses [4,5] and the need for pain relief is of its greater importance. With that, further studies ascertaining whether music would still offer pain relief/reduction during the late phases maybe conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the result of this study could support the use of soothing music together with other nursing interventions in reducing the pain experienced by women during the latent phase of labor. However, it is essential to note that music intervention was administered only during the latent phase of labor, pain increases as labor progresses [4,5] and the need for pain relief is of its greater importance. With that, further studies ascertaining whether music would still offer pain relief/reduction during the late phases maybe conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse interventions such as pharmacologic methods, acupressure, biofeedback, aromatherapy, hypnosis, relaxation techniques, breathing technique, massage, and warm shower have been used to relieve labor pain [2,5,34,35] . There is more evidence to support the efficacy of pharmacological methods, but they have more adverse effects [33] .…”
mentioning
confidence: 99%
“…Most previous studies found that massage therapy techniques were effective in LP alleviation (49)(50)(51)(52)(53)(54)(55)(56)(57)(58). A study showed that although massage therapy could alleviate LP during the first and second stages of labor, it had no significant effects on LP in the third stage of labor (58).…”
Section: Massage Therapymentioning
confidence: 99%
“…A study with women in labor has shown that massage is an effective nursing intervention capable of mitigating pain and anxiety during childbirth, and that the participation of the partner in the massage may have a positive influence over the childbirth experience (14) .…”
Section: Controlmentioning
confidence: 99%
“…Research evaluating the effect of breathing and relaxation techniques on pain and anxiety during parturition concluded that the techniques applied did not reduce the intensity of the pain, but promoted longer maintenance of low anxiety levels (14) . The effects of maternal mood swings, such as depression and anxiety, during pregnancy on the emotional and psychological development of the child remain unclear.…”
Section: Controlmentioning
confidence: 99%